A Clinicopathological and Molecular Analysis of Sellar/Suprasellar Neurocytoma Mimicking Pituitary Adenoma - Zhang, Lifeng; Fu, Weiwei; Zheng, Limei; Song, Fangling; Chen, Yupeng; Jiang, Changzhen; Xing, Zhen; Hu, Chengcong; Ye, Yuhong; Zhang, Sheng; Yan, Xiaorong; Wang, Xingfu (Frontiers in Endocrinology, 2022)
Objective: To investigate the clinicopathological characteristics, molecular genetic characteristics and prognosis of extraventricular neurocytoma located in the sellar/suprasellar region. Methods: Seven archived tumor samples derived from 4 patients with neurocytoma in the sellar/suprasellar region were collected from the First Affiliated Hospital of Fujian Medical University and the Affiliated Hospital of Qingdao University and retrospectively analyzed for clinical manifestations, imaging features, and histopathological features. Neuronal and pituitary biomarkers and molecular features were detected in these tumor tissues by immunohistochemistry and FISH or Sanger sequencing. The related literature was reviewed. Results: Three patients were female, while 1 was male, with an average age of 35.5 years . The initial manifestations were mainly headache and blurred vision in both eyes. The first MRI examination showed marginally enhancing masses in the intrasellar or intra- to suprasellar region. The diagnosis of pituitary adenomas was based on imaging features. The levels of pituitary hormones were normal. Histologically, the tumor cells were arranged in a sheet-like, monotonous architecture and were uniform in size and shape with round to oval, exquisite and hyperchromatic nuclei, which densely packed close to one another and were separated only by a delicate neuropil background. There was no evident mitosis, necrosis or microvascular proliferation. The three cases of recurrent tumors were highly cellular and showed increased mitotic activity. Immunohistochemically, the tumor cells were positive for syn, CR, CgA, NeuN, and vasopressin and were focally positive for GFAP, TTF-1, NF, CK8, vimentin and S100 proteins. Other markers, including IDH1, BRAF VE1, Olig-2, and EMA, were negative. Pituitary transcription factors and anterior pituitary hormones were negative. Molecular genetic testing showed that the tumor cells lacked IDH gene mutations, LOH of 1p/19q, MYCN amplification and EGFR alteration. With a median follow-up of 74.5 months (range 23 to 137 months), 3 patients relapsed at 11, 50 and 118 months after the initial surgery. Conclusion: The morphological features and immunophenotypes of neurocytoma in the sellar/suprasellar region are similar to those of classic central neurocytoma. The prognosis is relatively good. Gross-subtotal resection and atypical subtype may be related to tumor recurrence.